Azimuthal anisotropy of jet particles in p-Pb and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, S.; Adamova, D.; Adler, A.; Rinella, G. Aglieri; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (SPRINGER, 2024)
The azimuthal anisotropy of particles associated with jets (jet particles) at midrapidity is measured for the first time in p-Pb and Pb-Pb collisions at root sNN = 5.02 TeV down to transverse momentum (p(T)) of 0.5 GeV/c and 2 GeV/c, respectively, with ALICE. The results obtained in p-Pb collisions are based on a novel three-particle correlation technique. The azimuthal anisotropy coefficient v(2) in high-multiplicity p-Pb collisions is positive, with a significance reaching 6.8 sigma at low p(T), and its magnitude is smaller than in semicentral Pb-Pb collisions. In contrast to the measurements in Pb-Pb collisions, the v(2) coefficient is also found independent of p(T) within uncertainties. Comparisons with the inclusive charged-particle v(2) and with AMPT calculations are discussed. The predictions suggest that parton interactions play an important role in generating a non-zero jet-particle v(2) in p-Pb collisions, even though they overestimate the reported measurement. These observations shed new insights on the understanding of the origin of the collective behaviour of jet particles in small systems such as p-Pb collisions, and provide significant stringent new constraints to models.
Keywords: Heavy Ion Experiments; Jets; Particle Correlations and Fluctuations; PARTON; FLOW; Physics